2022
DOI: 10.3168/jds.2022-22108
|View full text |Cite
|
Sign up to set email alerts
|

Role of sortilin 1 (SORT1) on fatty acid–mediated cholesterol metabolism in primary calf hepatocytes

Abstract: Ketosis is a common metabolic disorder in peripartal dairy cows that is caused by excessive mobilization of fat and incomplete hepatic metabolism of fatty acids (FFA). Recent data in nonruminant models revealed that sortilin 1 (SORT1) is involved in a variety of lipid metabolism-related diseases. It plays important roles in the regulation of triglyceride (TAG) and total cholesterol (TC) levels. In this study, we first used liver biopsies from healthy cows (serum β-hydroxybutyrate concentration <0.6 mM) and cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…CE is involved in the storage and transport of cholesterol, which involves two main pathways within cells . First, CE can participate in lipid droplet formation by interacting with PLIN2, TG, phospholipids, and other substances, and ACATs play a key role in this process. In a study on glioblastoma, the inhibition of ACAT1 expression was found to suppress the synthesis of lipid droplets . Second, CE is a major component of VLDL and LDL, both of which are involved in transporting TG synthesized in the liver to the peripheral circulation .…”
Section: Discussionmentioning
confidence: 99%
“…CE is involved in the storage and transport of cholesterol, which involves two main pathways within cells . First, CE can participate in lipid droplet formation by interacting with PLIN2, TG, phospholipids, and other substances, and ACATs play a key role in this process. In a study on glioblastoma, the inhibition of ACAT1 expression was found to suppress the synthesis of lipid droplets . Second, CE is a major component of VLDL and LDL, both of which are involved in transporting TG synthesized in the liver to the peripheral circulation .…”
Section: Discussionmentioning
confidence: 99%